2013
DOI: 10.18438/b8d03m
|View full text |Cite
|
Sign up to set email alerts
|

Data-Driven Decision Making: An Holistic Approach to Assessment in Special Collections Repositories

Abstract: 2013 Griffin, Lewis, and Greenberg. This is an Open Access article distributed under the terms of the Creative Commons-Attribution-Noncommercial-Share Alike License 2.5 Canada (http://creativecommons.org/licenses/by-ncsa/2.5/ca/), which permits unrestricted use, distribution, and reproduction in any medium, provided the original work is properly attributed, not used for commercial purposes, and, if transformed, the resulting work is redistributed under the same or similar license to this one. AbstractObjective… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 13 publications
(12 reference statements)
0
5
0
Order By: Relevance
“…The authors concluded that “academic branch libraries can still be important destinations that continue to support students in their research and learning activities;” they also acknowledged that “as user and campus needs change so must branch libraries” (p. 211). Similarly, Griffin et al . (2013) conducted a holistic study of the Special and Digital Collections unit at the University of South Florida Tampa Library.…”
Section: Literature Reviewmentioning
confidence: 66%
See 1 more Smart Citation
“…The authors concluded that “academic branch libraries can still be important destinations that continue to support students in their research and learning activities;” they also acknowledged that “as user and campus needs change so must branch libraries” (p. 211). Similarly, Griffin et al . (2013) conducted a holistic study of the Special and Digital Collections unit at the University of South Florida Tampa Library.…”
Section: Literature Reviewmentioning
confidence: 66%
“…The authors concluded that "academic branch libraries can still be important destinations that continue to support students in their research and learning activities;" they also acknowledged that "as user and campus needs change so must branch libraries" (p. 211). Similarly, Griffin et al (2013) conducted a holistic study of the Special and Digital Collections unit at the University of South Florida Tampa Library. The assessment strategy was holistic in the sense that they created a model that "takes into account the needs, requirements, and standards of public services, technical services, and administration" (p. 228).…”
Section: Literature Reviewmentioning
confidence: 99%
“…22 Griffin, Lewis, and Greenberg argue that the need to "identify a comprehensive, integrated assessment strategy to better focus diminished resources" is necessary in light of shrinking library budgets and reduced staffing, particularly within the context of special collections repositories. 23 Their 2013 study examined the University of South Florida (USF) Tampa Library, wherein Special & Digital Collections developed a holistic, systematic, assessment strategy "to improve a range of services in the Department." 24 By applying several quantitative and qualitative assessment tools, including Desk Tracker statistics and Reading Room Patron Surveys, they argued that library staff uncovered findings to propose user-centric modifications, including shifting reading room hours to meet patron needs, and continuing targeted outreach efforts.…”
Section: Literature Reviewmentioning
confidence: 99%
“…DL evaluations can also be combined with traditional library service assessment criteria for holistic evaluation. The University of South Florida Tampa Library developed a holistic assessment including data from Aeon (their material request and workflow management software), Desk Tracker, reading room patron surveys, Web site and digital collections usability testing, Web analytics, and Fedora Commons analytics (Griffin, Lewis, and Greenberg 2013). Utilizing multiple assessment methods allowed for improved Web navigation, optimized DL performance for Internet Explorer and mobile devices (determined to be heavily adopted by users), the development of digitization priorities, and outreach opportunities based on little-used physical collections with high Web views (Griffin,Lewis,and Greenberg,(234)(235).…”
Section: Holistic Approach To DL Assessmentmentioning
confidence: 99%